Integrated Approach for the Effective Management of Rust and Spot Blotch of Wheat: Integrated management of wheat foliar diseases - Monisha L; M. Hegde, Gurudatt; Ashtaputre, S. A. (Journal of Cereal Research, 2025)
Foliar diseases such as spot blotch, stem rust and leaf rust are the major devastating diseases causing significant yield loss in wheat growing regions worldwide. Integration of bio rationals in a spray schedule, being cost effective and environment friendly approach serves as important components of integrated disease management strategy. Among the various spray schedules evaluated under field conditions, combi product fungicide (hexaconazole 5 % + captan 70 %) 75 % WP @ 0.2 per cent - (hexaconazole 5 % + captan 70 %) 75 % WP @ 0.2 per cent was found to be highly effective in managing the diseases (Spot blotch-13.71%, stem rust-9.93CI, leaf rust-2.93CI, grain yield-29.65 q/ha and B: C ratio-3.04). Whereas, under integrated spray schedules, (hexaconazole 5 % + captan 70 %) 75 % WP @ 0.2 per cent – Trichoderma harzianum (MH027645.1) @ 1 per cent was found to be effective (Spot blotch-18.32%, stem rust-18.40 CI, leaf rust – 4.80 CI, grain yield - 22.86 q/ha and B: C ratio - 2.39) and exhibited SPAD value of 37.85.